Incidence and Circumstances of Accounting Errors - DeFond, Mark L.; Jiambalvo, James (The Accounting Review, 1991)
[Accounting Principles Board (APB) Statement No. 20 (1971) defines financial statement errors as items resulting "from mathematical mistakes, mistakes in the application of accounting principles, or the oversight or misuse of facts that existed at the time the financial statements were prepared" (APB 20, par. 13). This definition encompasses both intentional and unintentional misrepresentation by management. Errors affecting previously reported earnings are revealed as prior period adjustments as specified in Statement of Financial Accounting Standards No. 16 (1977). If the erroneous year's financial statements are presented, retroactive restatement is required (in accordance with APB 9 1966). Footnote disclosure of the nature of the error and its effect on earnings, earnings before extraordinary items, and earnings per share is also required. Although financial statement disclosures generally provide no indication that prior errors were intentional, they may be motivated by the same types of economic incentives influencing managers' choices of accounting methods or management of accruals. In this study, we examine the incidence of accounting errors revealed by prior period adjustments for 41 firms in comparison with a control group of another 41 firms. This comparison is used to highlight circumstances that are likely to motivate managers to use errors as an income management tool. While corrections of prior year earnings are rare for both over- and understatement errors, the latter are relatively less frequent. Our investigation revealed 41 overstatement firms but only three understatement firms, which is consistent with an income-increasing motivation. Because of the very small number of understatements, the analysis is limited to overstatement errors. We find that the earnings overstatements are negatively correlated with the growth in earnings. Analysis also indicates that earnings overstatements are more likely when firms have diffuse ownership, lower growth in earnings, and fewer income-increasing GAAP alternatives available. Overstatements are less likely among firms that have audit committees. These results are generally consistent with the view that overstatement errors are the result of managers responding to economic incentives.]